2018
DOI: 10.1037/edu0000243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early grade retention on school completion: A prospective study.

Abstract: This 14 year prospective study investigated the effect of retention in grades 1–5 on high school completion (diploma, GED, or drop out). Participants were 734 (52.7% males) ethnically diverse, academically at-risk students recruited from Texas schools into the study when they were in first grade (mean age = 6.57). Propensity score weighting successfully equated the 256 retained students and the 478 students continuously promoted students on 65 covariates assessed in grade 1. At the end of 14 years, 477 had ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 90 publications
(129 reference statements)
0
23
0
Order By: Relevance
“…First, the tutorial utilizes only logistic regression without any interaction terms and examines only the SMDs to assess covariate balance. As a note, the tutorial replicated the logistic regression method which yielded best covariate balance in the original study (Hughes et al., ). Also, the original analysis reported that variance ratio (VR) statistics for all covariates after weighting were within the recommended (0.5, 2.0) range for well‐balanced covariates.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…First, the tutorial utilizes only logistic regression without any interaction terms and examines only the SMDs to assess covariate balance. As a note, the tutorial replicated the logistic regression method which yielded best covariate balance in the original study (Hughes et al., ). Also, the original analysis reported that variance ratio (VR) statistics for all covariates after weighting were within the recommended (0.5, 2.0) range for well‐balanced covariates.…”
Section: Discussionmentioning
confidence: 94%
“…After careful consideration and discussions between content and methodological experts, in total, sixty‐four baseline covariates were selected as baseline covariates to predict the PS to retain a grade. The baseline covariates included standardized performance scores, parent, child, and classmate responses on the target child's characteristics, and school‐level data (more details are given in Hughes et al., ). A binary logistic regression was used for the PS estimation model.…”
Section: Propensity Score Analysis Data Examplementioning
confidence: 99%
See 2 more Smart Citations
“…Details on study procedures for tracking students’ graduation status are reported in Hughes, West, Kim, and Bauer ().…”
mentioning
confidence: 99%